2021
DOI: 10.1080/10410236.2021.1910166
|View full text |Cite
|
Sign up to set email alerts
|

A Subjective Culture Approach to Cancer Prevention: Rural Black and White Adults’ Perceptions of Using Virtual Health Assistants to Promote Colorectal Cancer Screening

Abstract: In the US, Black adults are less likely than White adults to be screened for colorectal cancer (CRC). This study uses a subjective culture approach to describe and compare perceptions of a CRC screening intervention delivered via virtual health assistants (VHAs) among rural Black and White study participants. We analyzed 28 focus groups with Black (n = 85) and White (n = 69) adults aged 50-73. Participants, largely recruited through community engagement efforts, tested the VHA intervention on mobile phones pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The advantages of adapting virtual agents to participants have been demonstrated in several studies. For instance, in Vilaro et al ( 2021 ), participants (all Black women) liked Black female agents for being artificial, hence creating a sense of trust and freedom where participants could avoid inherent biases and racism. In virtual learning environments, research has shown the impact of virtual agents' gender on human-agent interactions (refer to Section 3.4).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of adapting virtual agents to participants have been demonstrated in several studies. For instance, in Vilaro et al ( 2021 ), participants (all Black women) liked Black female agents for being artificial, hence creating a sense of trust and freedom where participants could avoid inherent biases and racism. In virtual learning environments, research has shown the impact of virtual agents' gender on human-agent interactions (refer to Section 3.4).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the VHC they interacted with, individuals with a higher rural identity had more positive impressions of appearance. Prior work suggests rural adults prefer VHCs seen as calm and with a smiling and inviting face ( Vilaro et al, 2021a ). The current study suggests adults with high rural identity may be even more attuned to VHC appearance, possibly due to sociocultural norms for rurality that value virtual agents being similar to community members as a credibility indicator ( Mendu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be reasoned that shared negative experiences with rural healthcare systems (e.g., structural racism, discrimination) foster a strong sense of rural belonging among Black adults ( Fowler-Brown et al, 2006 , Hammonds and Reverby, 2019 ). More specifically, rural Black adults may attend more closely to VHC features such as clothing and perceived professionalism ( Vilaro et al, 2021a ). This differential effect based on race may be explained by the fact that identifying as both Black and rural represents two stigmatized identities, creating a novel intervention response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some rural communities, cultural factors may be manifested more subjectively and interrelated with race ( 25 , 26 ). Research conducted among rural Black and White adults from North Florida showed that cultural factors manifested into preferences on how patients wanted to be engaged with the health-care system, and these preferences were also intertwined with race ( 27 ).…”
Section: Cbpr Considerations In Rural Settingmentioning
confidence: 99%